Systematic evaluation of suspension MDCK cells, adherent MDCK cells, and LLC-MK2 cells for preparing influenza vaccine seed virus. Issue 43 (8th October 2019) - Nakamura, Kazuya; Harada, Yuichi; Takahashi, Hitoshi; Trusheim, Heidi; Bernhard, Roth; Hamamoto, Itsuki; Hirata-Saito, Asumi; Ogane, Teruko; Mizuta, Katsumi; Konomi, Nami; Konomi, Yasushi; Asanuma, Hideki; et al.
Abstract: Suspension Madin–Darby canine kidney (MDCK) cells (MDCK-N), adherent MDCK cells (MDCK-C), and adherent rhesus monkey kidney LLC-MK2 cells (LLC-MK2D) were systematically evaluated for the preparation of influenza vaccine seed viruses for humans on the basis of primary virus isolation efficiency, growth ability, genetic stability of the hemagglutinin (HA) and neuraminidase (NA) genes, and antigenic properties in hemagglutination inhibition (HI) test of each virus isolate upon further passages. All the subtypes/lineages of influenza viruses (A(H1N1), A(H1N1)pdm09, A(H3N2), B-Victoria, and B-Yamagata) were successfully isolated from clinical specimens by using MDCK-N and MDCK-C, whereas LLC-MK2D did not support virus replication well. Serial passages of A(H1N1) viruses in MDCK-N and MDCK-C induced genetic mutations of HA that resulted in moderate antigenic changes in the HI test. All A(H1N1)pdm09 isolates from MDCK-C acquired amino acid substitutions at the site from K153 to N156 of the HA protein, which resulted in striking antigenic alteration. In contrast, only 30% of MDCK-N isolates showed amino acid changes at this site. The frequency of MDCK-N isolates with less than two-fold reduction in the HI titer was as high as 70%. A(H3N2) and B-Yamagata isolates showed high antigenic stability and no specific amino acid substitution during passages in MDCK-N and MDCK-C. B-Victoria isolates from MDCK-N and MDCK-C acquired genetic changes at HA glycosylation sites that greatly affected their antigenicity. When these cell isolates were applied to passages in hen eggs, A(H1N1), B-Victoria, and B-Yamagata viruses grew well in eggs, while none of the cell isolates of A(H3N2) viruses did. Thus, we demonstrate that MDCK-N might be useful for the preparation of influenza vaccine seed viruses.